Knowledge spillovers – Mobility of highly educated workers within high technology sector in Finland - Kirsi Mukkala (European Regional Science Association (ERSA), 2005)
The economic development and technological progress of a region are highly dependent on the accumulation and diffusion of knowledge. There are numerous channels through which knowledge might be transmitted. In this study, it is assumed that regional mobility of highly educated and innovative intensive workers between firms, organisations or institutions secures the diffusion and circulation of the knowledge. Hence, this analysis will concentrate on the regional job flows of individuals working in the high technology sector. The main topics of interest are: (1) to analyse the personal and household characteristics of the typical highly educated migrants within high technology sector, and (2) to evaluate the rate of labour turnover in different sub-sectors and regions. The empirical analysis of the paper is based on data from the Finnish Longitudinal Census File. Methodologically, the worker flows between regions are modelled by the maximum likelihood estimation which employs cross-sectional binary logit model, based on logistic distribution.
Keywords: 330